How Do Trauma and Identity Unfold Through Dialogue? A Psychoanalytic and Linguistic Analysis of Netflix's Slasher Solstice - Fajar Nadeem; Seemab Jamil Ghouri (WISE Pendidikan Indonesia, 2024)
This study aims to explore the relationship between trauma, desire, and identity through language patterns in the Netflix series Slasher: Solstice. Using a psychoanalytic and linguistic analysis approach, the research delves into how characters' dialogues and speech styles reflect their psychological states, particularly in confronting past traumas. The study employs a qualitative method with observational analysis of the interactions and dialogues of the main characters within the series. The results reveal that speech patterns, word choice, and intonation provide deep insights into the characters' psychological conditions. For instance, the character Connor displays aggressive and fragmented speech patterns as a defense mechanism against trauma, while the character Sadia exhibits emotional control through structured and formal language. This research offers a new perspective by combining psychoanalytic and linguistic approaches to understand character development within the horror genre. The analysis reveals that shifts in language style, as the narrative unfolds, indicate a transformation in the characters' identities, increasingly shaped by trauma and internal conflict.